Inovação, novos conceitos ampliados: oportunidades para empresas - Morgado, Eduardo Martins [UNESP] (2011)
This article describes the evolution of Innovaton concepts, specifically Technological Innovation. It seeks to demonstrate that this conceptual evolution opens new paths for the development of Innovations and for the creation of Competitive Opportunities. It presents a model for searching and assessing the risk of these innovations regarding the adopted Technologies and the targeted market. A traditional tool for the Adoption of Innovations is introduced to be used in risk assessment. We seek to propose a strategy to search for, to identify and to assess innovations based on the involvement of the entire organization, by means of activities guided by creativity. Important aspects regarding the process of adopting Innovations are described to demonstrate the importance of the "time" dimension, as well as to contribute for the Innovation search practice.